The effect of mindfulness based psychoeducation program on adolescents' character strengths, mindfulness and academic achievement - SATAN, AYŞİN (SPRINGER, 2022)
The research was conducted to prepare a mindfulness-based psychoeducation program for adolescents and to test the effect of the program on character strengths, mindfulness levels, and academic achievement of high school students. The study was designed as mixed-method research, and consisted of two stages. In the first stage, the relationship between mindfulness, character strengths, and academic achievement was investigated. According to the findings, 24.5% of the variance in grade point average was predicted by mindfulness and three character strengths including persistence, prudence, and openness to learning. In the second stage, a mindfulness-based psychoeducation program was developed and its effects on high school students' perseverance, prudence, love of learning character strengths, mindfulness, and academic achievements were examined in a pretest- posttest randomized control group design. According to results, the 8-week mindfulness-based psychoeducation program increased the level of mindfulness of participants, while partially increasing their three character strengths, and academic achievement.
Keywords: Mindfulness; Character strengths; Positive psychology; Achievement; STRESS REDUCTION PROGRAM; ANXIETY; INTERVENTION; PERFORMANCE; MEDITATION; PSYCHOLOGY; ATTENTION; TRIAL